2019
DOI: 10.7759/cureus.5332
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Anterior Lumbar Interbody Fusion for Discogenic Chronic Low Back Pain in a Short-stay Setting: Data From a Prospective Registry

Abstract: IntroductionAs a possible treatment option for chronic lower back pain (CLBP) due to single-level degenerative disc disorder (DDD), the efficacy of anterior lumbar interbody fusion (ALIF) has been reviewed various times in the existing literature. Nevertheless, a scarcity of data exists pertaining to ALIF procedures carried out in a short-stay setting using an Enhanced Recovery after Surgery (ERAS) protocol, particularly concerning the safety.MethodsProspectively collected data are analyzed to study the effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…However, the underlying mechanism for this deficit was not explained or explored. 37 A case series of 2 patients by Saini et al demonstrated S1 radiculopathy after L5-S1 ALIF with stand-alone constructs. The culprit in both cases was identified as nerve root impingement due to a protruding screw tip.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanism for this deficit was not explained or explored. 37 A case series of 2 patients by Saini et al demonstrated S1 radiculopathy after L5-S1 ALIF with stand-alone constructs. The culprit in both cases was identified as nerve root impingement due to a protruding screw tip.…”
Section: Discussionmentioning
confidence: 99%
“…All surgical procedures were performed by a single senior neurosurgeon (M.L.S.) as described previously [43,47,48,51,53]. Due to local restrictive regulations by insurance companies, patients aged > 80 or with a body mass index (BMI) > 33 or American Society of Anaesthesiologists (ASA) score > 2 cannot be considered for elective short-stay spine surgery [49].…”
Section: Designmentioning
confidence: 99%
“…Within the surgical options for the treatment of LDDD, anterior lumbar interbody fusion (ALIF) plays a crucial role given its ability to improve segmental and global lordosis of the intervened region, also generating adequate foraminal and spinal canal decompression with a low complication profile [6] , [7] , [8] , [9] . The most frequently ALIF intervened level is L5-S1 [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%